2022
DOI: 10.1136/ip-2022-044598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of speed humps on injury consequences on trunk roads traversing towns in Ghana: A quasi-experimental study

Abstract: BackgroundSpeed calming interventions have been employed globally as a road safety measure to curb outcomes of RTCs such as injuries and deaths. In Ghana, few studies have reported on the effect of speed calming measures on the severity of road traffic injuries. This study examined the effect of speed humps on the severity of injuries during RTCs on trunk roads passing through towns in Ghana from 2011 to 2020.MethodsThe study employed a quasi-experimental before-and-after study with controls design to answer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, when pedestrian and cyclist crashes was studied separately, only non-significant reductions of crashes were found. In a recent before-and after study of speed bumps in 50 km/h speed zones in Ghana, an overall reduction of 77% of police reported injury crashes was observed (Gyaase et al, 2023). The present study observed significant reductions in injury severity for both bicyclists and pedestrians, results that add new knowledge to this field of research.…”
Section: Discussionsupporting
confidence: 71%
“…However, when pedestrian and cyclist crashes was studied separately, only non-significant reductions of crashes were found. In a recent before-and after study of speed bumps in 50 km/h speed zones in Ghana, an overall reduction of 77% of police reported injury crashes was observed (Gyaase et al, 2023). The present study observed significant reductions in injury severity for both bicyclists and pedestrians, results that add new knowledge to this field of research.…”
Section: Discussionsupporting
confidence: 71%
“…Existing measures, especially speed-related, are questioned for their effectiveness and suitability in prior literature. Despite studies showing speed bumps reduce injuries and deaths [26,53,60], excessive speeding remains common [61] due to ad hoc implementation based on varying factors rather than standardized guidelines [26,62]. Consequently, reports of poor road safety measures and their negative effects have led to speed bump relocation or removal on major roads [27,52] and calls for speed calming measures to be restricted to residential streets, rather than high-speed arterial roads [26,63].…”
Section: Plos Onementioning
confidence: 99%
“…Proposed solutions align with global evidence-based practices including traffic calming [60,67], improved road designs [40,68], warning signs about hazards [69], roadside and central barrier systems [70,71], and the separation of road users such as pedestrians [72][73][74], cyclists [75][76][77], and motorcycle occupants [78,79]. The socioeconomic environment solutions addressed prehospital care, crucial for minimizing crash-related harm [80].…”
Section: Plos Onementioning
confidence: 99%
“…Chandra, Begum and Sekhar (2022) observed that for SB with a parabolic design the vehicle speed at the crown of the SB presented great values (13 to 28 km/h) than for those with circular design (5 to 21 km/h). Reduction in crashes was also a well established point regarding SB implementation (Gyaase et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 98%